Shearwaters know the direction and distance home but fail to encode intervening obstacles after free-ranging foraging trips. - Padget, O; Stanley, G; Willis, J; Fayet, A; Bond, S; Maurice, L; Shoji, A; Dean, B; Kirk, H; Juarez-Martinez, I; Freeman, R; Bolton, M; et al. (National Academy of Sciences, 2019)
While displacement experiments have been powerful for determining the sensory basis of homing navigation in birds, they have left unresolved important cognitive aspects of navigation such as what birds know about their location relative to home and the anticipated route. Here, we analyze the free-ranging Global Positioning System (GPS) tracks of a large sample (n = 707) of Manx shearwater, Puffinus puffinus, foraging trips to investigate, from a cognitive perspective, what a wild, pelagic seabird knows as it begins to home naturally. By exploiting a kind of natural experimental contrast (journeys with or without intervening obstacles) we first show that, at the start of homing, sometimes hundreds of kilometers from the colony, shearwaters are well oriented in the homeward direction, but often fail to encode intervening barriers over which they will not fly (islands or peninsulas), constrained to flying farther as a result. Second, shearwaters time their homing journeys, leaving earlier in the day when they have farther to go, and this ability to judge distance home also apparently ignores intervening obstacles. Thus, at the start of homing, shearwaters appear to be making navigational decisions using both geographic direction and distance to the goal. Since we find no decrease in orientation accuracy with trip length, duration, or tortuosity, path integration mechanisms cannot account for these findings. Instead, our results imply that a navigational mechanism used to direct natural large-scale movements in wild pelagic seabirds has map-like properties and is probably based on large-scale gradients.